Simultaneous or successive resections of pancreas and colon due to tumors of both organs, colon carcinomas infiltrating duodenum and caudal pancreas invading left colon - Praderi, Raúl C; Harretche, Martín; Estefan, Alberto; Parodi, her; Hernández, Walter; Boudrandi, Sonia; Navarrete, Héctor (Cirugía del Uruguay, 1998)
Two patients with cancer of the right colon fistulized in duodenum underwent simultaneous right hemico/ectomies and cephalic duodenopancreatectomies. There were no important post-operative complications and they are both alive eleven and ten years after surgery